2022
DOI: 10.1021/acsnano.2c01095
|View full text |Cite
|
Sign up to set email alerts
|

Pushing Down the Limit of NH3 Detection of Graphene-Based Chemiresistive Sensors through Functionalization by Thermally Activated Tetrazoles Dimerization

Abstract: An easy and cost-effective method is presented to functionalize graphene through thermally activated dimerization of 2,5-diaryltetrazoles. Consistently with the experimental spectroscopic results, theoretical calculations demonstrate that during the thermal treatment a dimerization process to tetrazine is energetically more favorable than covalent grafting. Since both the functionalization method by thermal activation and the use of tetrazoles have never been considered before to prepare graphene-based chemire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…A comparison with literature works has been performed in terms of sensitivity ( i.e. sensor response percentage normalized over the concentration: (Δ R / R 0 × 100)/[NH 3 ]) and detection limit: the results obtained for the five developed sensors are in line with both graphene-based sensors, 28,29,73–80 and reduced graphene oxide functionalized with metal phthalocyanine molecules, 81–84 as can be found in Table SVII †…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…A comparison with literature works has been performed in terms of sensitivity ( i.e. sensor response percentage normalized over the concentration: (Δ R / R 0 × 100)/[NH 3 ]) and detection limit: the results obtained for the five developed sensors are in line with both graphene-based sensors, 28,29,73–80 and reduced graphene oxide functionalized with metal phthalocyanine molecules, 81–84 as can be found in Table SVII †…”
Section: Resultsmentioning
confidence: 64%
“…A comparison with literature works has been performed in terms of sensitivity (i.e. sensor response percentage normalized over the concentration: (DR/R 0 × 100)/[NH 3 ]) and detection limit: the results obtained for the ve developed sensors are in line with both graphene-based sensors, 28,29,[73][74][75][76][77][78][79][80] and reduced graphene oxide functionalized with metal phthalocyanine molecules, [81][82][83][84] as can be found in Table SVII. † As for the sensing mechanisms, the resistance increase upon ammonia exposure indicates that the Gr, Gr_FePc, Gr_NiPc, and Gr_ZnPc layers are p-type, consistently with the fact that the electron injection from ammonia reduces the density of holes in these layers.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Carbon nanotubes have been largely studied as single sensors [ 26 , 27 , 28 ] and, even to a lesser extent, also as electronic noses [ 17 , 29 ], while, only in the past few years, graphene, thanks to its high sensitivity to the surface adsorption of gas molecules [ 30 ], its high in-plane conductivity, and its low electrical intrinsic noise [ 31 ], has attracted the interest or researchers working in the sensors field. Although recent studies have clearly demonstrated the possibility to develop highly sensitive graphene sensors after proper functionalization [ 32 , 33 , 34 , 35 , 36 , 37 ], still few are the works exploiting graphene to develop sensors array [ 38 , 39 , 40 ], especially in a chemiresistor configuration [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address the problems, various techniques such as chemosensors, colorimetric sensors, electrochemical methods, and sol–gel-based visualization have been used for the monitoring of them. These techniques, however, are hard to be widely used because they may suffer from some of the shortcomings such as a bulky instrument, slow response, low sensitivity, unfavorable reversibility, specially trained personnel, high cost, etc. Recently, metal–organic frameworks (MOFs), nanofibrous membranes, , and polymers were used to conduct the detection.…”
mentioning
confidence: 99%